A Collaborative Islamic Education Learning Model Based on Local Culture to Strengthen Students’ Social Character in Madrasah - Rinaldi Datunsolang; Najamuddin Petta Solong; Firman Sidik; Ritmon Amala; Djunawir Syafar; Ahmad Fakhrurrazi Bin Mohammed Zabidi; Safaah Restuning Hayati (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
This study aims to analyze the collaborative Islamic education learning model based on local culture in strengthening the social character of students in Madrasah Aliyah Negeri 2 Gorontalo Regency. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that collaborative learning based on local culture is applied through group discussions, social projects, and reflection on Islamic values that are integrated with the local culture of Gorontalo, especially the value of huyula which emphasizes cooperation, empathy, and responsibility. This model contributes to increasing student learning participation while strengthening social character, such as tolerance, solidarity, and social concern. The strengthening is supported by the culture of mutual cooperation and madrasah leadership in creating a conducive learning environment. This study confirms that the collaborative Islamic Education learning model based on local culture is effective in integrating cognitive, affective, social, and spiritual aspects to shape the social character of students in madrasah.